Kajian kemudahsampaian di kawasan perumahan : kajian kes Taman Ria Jaya, Sg. Petani, Kedah Darulaman - Baharom, Mohammad Nasir (2001)
Accessibility is one of the most important aspects in a residential area. It has to be developed concurrently with the overall development. Short cut, far distance to working place, social amenities and other elements of urban development can cause hassle to urban .. dwellers. This research intends to study the perception of residents of a housing area on the accessibility built in their surrounding. A total of 290 numbers of residential units bas been chosen as the research sample. Sampling was done through systematic method. Research shows that the majority of resident express their dissatisfaction with the accessibility developed in their residential area. Nevertheless there are residential who feels that the accessibility in their residential area is satisfactory.